Purification of kojic acid - Ariff, Arbakariya (2012)
The present invention provides a method of purifying kojic acid from fermentation broth by repeated crystallization in solvents to obtain suitable kojic acid crystal size and structure, which is free from impurities such as pigments, metals and the like. Accordingly, the present method comprises the steps of: (i) obtaining kojic acid solution from a fermentation broth; (ii) dissolving the kojic acid solution in a solvent or a mixture of solvents with appropriate volume to maintain the kojic acid solution at a concentration of 80 g/l to 100 g/l; (iii) agitating the concentrated kojic acid solution at 50 to 100 rpm; (iv) removing the solvent or mixture of solvents contained in the concentrated kojic acid solution by way of evaporation at 50°C to 80°C; (v) maintaining the temperature of the concentrated kojic acid solution at 5°C to 35°C for up to 10 hour to form kojic acid crystals; (vi) separating the kojic acid crystals; and (vii) repeating the steps of (ii) through (vi) for more than once in order to form high purity kojic acid crystals, which are free from impurities.